Phonological facilitation in picture naming: When and where? A tDCS study. (3rd June 2017) - Pisoni, Alberto; Cerciello, Milena; Cattaneo, Zaira; Papagno, Costanza
Highlights: Phonological facilitation was investigated by anodal tDCS over the LIFG and LSTG. LSTG stimulation reduced PF, while LIFG did not modulate this effect. PF may occur after lexical selection, and inhibitory processes may be involved. While semantic interference is pre-lexical, the mechanism underlying this effect and PF may be the same. Abstract: Phonological facilitation (PF) refers to a reduction of naming latencies when a phonologically related word is presented concurrently with the target picture, as compared to the presentation of phonologically unrelated words. According to spread of activation models of word production, this effect arises after lexical selection, during phonetic encoding, and is due to the co-activation of the phonemes shared by the target word and the distracter. Conversely, semantic interference (SI) is characterized by longer naming latencies when semantically related distracters are concurrently presented with the target picture. This effect seems to arise before lexical selection. However, alternative hypotheses postulate that PF and SI both arise at a post lexical level. In this study, we aim to shed light on this debate by investigating the neural correlates of the PF and by comparing these results with those of previous studies on SI. In two experiments, we applied anodal transcranial direct current stimulation (tDCS) over the left superior temporal gyrus (LSTG) and left inferior frontal gyrus (LIFG) before a picture-word interference task in which auditory distracters, which could be phonologically related or unrelated, were presented at a SOA of 150 ms or 300 ms. While stimulating the LSTG significantly reduced the PF by decreasing RTs in phonologically unrelated trials, anodal tDCS over the LIFG did not affect PF. In line with previous results, our findings support the "activation by competition" model, pointing to inhibition between target and distracters nodes as the mechanism involved in the occurrence of PF and SI.